Effect of timing of artificial insemination with conventional or sex-sorted semen on fertility of lactating dairy cows - V.G. Santos; P.D. Carvalho; A.H. Souza; S. Priskas; J.A.L. Castro; A.M.F. Pereira; P.J. Ross; J. Moreno; M.C. Wiltbank; P.M. Fricke (Journal of Dairy Science)
ABSTRACT: The effect on pregnancy per artificial insemination (P/AI) of interval from induction of ovulation to timed artificial insemination (TAI) for cows submitted to a fertility program and the interval from the onset of estrous alert to artificial insemination (AI) for cows inseminated to estrous alert was analyzed in 3 experiments. In experiment 1, multiparous lactating Holstein cows (n = 1,924) from 6 herds were submitted to a Double-Ovsynch protocol to receive their first TAI using conventional semen. On the day of the last GnRH treatment, cows were randomly assigned to TAI at the time of the last GnRH treatment (Cosynch-56: 0 h) or TAI 16 h after the last GnRH treatment (Ovsynch-56: 16 h). Ovsynch-56 cows had more P/AI than Cosynch-56 cows (46% vs. 36%) 32 d after TAI. In experiment 2, lactating Holstein cows (n = 13,318) from 2 herds were submitted to a Double-Ovsynch protocol to receive their first TAI (n = 14,089; during more than one year) or to a GGPPG protocol for second and greater TAI (n = 6,806) using either sex-sorted Holstein semen or conventional beef semen. Overall, TAI varied from 13 to 23 h after the last GnRH treatment, and there was no linear or quadratic effect of time from the last GnRH treatment to TAI on P/AI 32 d after TAI for cows receiving AI with sex-sorted Holstein semen or conventional beef semen. In experiment 3, lactating dairy cows (n = 10,927) were fitted with an activity-monitoring tag mounted to a neck collar, and the timing of AI relative to the onset of estrous alert was recorded. Timing of AI varied from 0 to 40 h after the onset of estrous alert, and there were both linear and quadratic effects of interval from the onset of estrous alert to AI in which cows inseminated early (≤3 h) or late (≥24 h) after the onset of estrous alert had fewer P/AI 32 d after AI than cows inseminated 13 to 23 h after the onset of estrous alert. We conclude that lactating dairy cows inseminated too early relative to a synchronized ovulation or too early or too late relative to the onset of estrous alert had fewer P/AI than cows inseminated from 13 to 23 h. Further, optimal timing of AI relative to a synchronized ovulation or the onset of estrous alert in lactating dairy cows did not differ between conventional and sex-sorted semen.